Recommendations, best practices and key factors of smart city and smart citizenship - Katalin FEHER; Boros ISTVÃN (Smart Cities and Regional Development Journal)
Objectives The goal of the paper is to present an overview of current and future-oriented smart city concepts with particular consideration of smart citizenship. Prior work The evolution of the academic references is considered regarding the subject area. Approach Based on a systematically filtered governmental, business and university research corpus, a global insight is synthesised. Results Applying text network analysis, key factors and best practices of smart cities were mapped. The resulted summary provides the future smart city developments and the smartification of citizenship. Beyond, the analysis has explored unexpected essential metaphors from rainforest to backbone providing a specific overview of smart city and smart citizens. Implications The resulted recommendations support the relevant strategy of the future city managements, and also, the upcoming and comprehensive academic analysis. Value The highlighted trends and metaphors contribute to the holistic view of smart city and smart citizenship by specific recommendations.